CRYSTAL SALT LAMP, AN AFFORDABLE EQUIPMENT - Milan, Chauhan; Jagmeet, Kaur; twinkle, Gupta (International Journal of Ayurveda and Pharma Research, 2015)
As we are proceeding to next century, along with all the comforts of life, we are getting hazardous effects, out of our luxurious life. In todays era, where no doubt technically we are getting stronger and on the other end this technology is definitely rendering us with some of the major side effects. we are constantly using and are in touch with the various equipments like mobile phones, laptops, LCDS, LEDS, oven, etc and various other devices, which are causing hazardous effects on us. Now since we belong to particular century where it becomes essential for one to use these common gadgets which are being commonly used by almost every one. To kill the hazardous and unwanted effects of these gadgets, crystal salt lamp is an easy and affordable answer for it. Mythologically, salt is considered as gift of god and is dear to god. In Ayurveda also there is detail explanation about salt and its uses and salt is widely used in almost all the various formulations in Ayurveda.